Analysis SWOT Strategy of the Ministry of Education and Culture's Rumah Belajar - Budiyanto, Arief; Sholeh, Achmad Nur (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2021)
The objectives of this study are (1) to analyze the potential and positioning of the MendDikBud Rumah Belajar, (2) to see the strategies applied by the Rumah Belajar and (3) to see the position of the MenDikBud Rumah Belajar on the TOWS-4K matrix. The method in this research is qualitative method. Data taken from interviews, observation and documentation. Data analysis was performed using 4 stages, namely data collection, data reduction, data presentation and drawing conclusions. The results of this study are the results of the SWOT Analysis of the Ministry of Education and Culture's Rumah Belajar on the IE matrix of the position of the MenDikBud Rumah Belajar which is in column V (five) with an IFAS value of 2.56 and an EFAS of 2.44, which means that the strategy that has been implemented so far has been good and can be maintained (Hold and Maintain). The conclusion in this study is that the position in the SWOT / TOWS-4K learning house matrix is ​​in quadrant I which means that the strategy that must be carried out is aggressively oriented, one example is to increase developing user growth and can also be done by developing existing products / services.